연안 여객선 내 안전요원 의무승선제도 도입과 법적지위 보장을 위한 법제도적 고찰 - 김현수; 김학범 (한국해양경찰학회보, 5(1), 2015)
이 연구의 목적은 국내 연안여객선의 안전한 운항을 도모하기 위하여 운항 중인 선박은 사전에 정한 기준에 따라 안전요원 승선을 의무화하여 안전한 연안여객선의 운항을 담보하고자 함에 있다. 지난 2014년 초 남해안 진도 앞바다에서 침몰한 세월호 사건은 승객의 가족과 전 국민들에게 크나큰 아픔을 가져왔다. 대양이 아닌 국내 연안에서 육지와 불과 수 킬로미터 떨어진 해상에서 여객선이 침몰하였고, 선박 내 승선하고 있던 승객을 적극적으로 구조하지 못하고 수학여행을 떠난 고등학생을 포함한 수많은 사람들이 차가운 물속에서 운명을 달리하였다. 일반적인 여객선 침몰사고가 대형사고의 결과를 초래하는 경우는 대부분 법제도의 미비와 해운사의 경제적 이익추구만을 내세우면서 승객의 초과승선 화물의 과다적재, 운항이 미숙한 운항요원의 배치 등이 총체적으로 문제가 되어 나타나게 된다. 본 세월호 사건의 경우도 법제도의 미비와 해운사의 이윤추구만을 위한 운항이 대참사를 가져온 근본적 원인이 되었다고 할 수 있다. 이와 같이 해양사고의 결과는 대형참사로 이어지는 경우가 많고, 공권력에 의한 적절한 조력을 받기에는 해상 기상 등의 변수가 많으므로 사전에 안전한 운항을 위한 제도의 마련이 필요하다. 특히 현재 국내 연안여객선의 이용률이 점차 증가하고 있고 지속적인 증가를 예측하고 있으므로 안전한 운항을 위한 제도의 마련이 시급하다 할 수 있다. 이러한 이유에 본 논문에서는 연안여객선의 안전한 운항을 위한 여러 제도 중 소위 안전요원의 의무승선제도의 도입과 안전요원의 법적지위의 부과를 위한 법률을 분석하였다. 국내 연안여객선을 운항하고 있는 대부분의 해운선사는 매우 열악한 재무구조를 가지고 있어 또 다른 비용이 필요로 하는 안전요원의 의무탑승제도의 도입을 희망하지 않을 수 있다. 그러나 사기업의 이익추구가 결국 이를 이용하는 국민의 안전을 위협할 수 있는 문제로 나타날 수 있다면 정부의 부작위 책임을 면할 수 없다고 할 것이다. 즉 국민의 안전을 위하여 정부와 관계기관은 보다 적극적인 해운정책의 수립과 집행이 필요하다. 이러한 이유에서 안전요원의 의무승선제도의 도입을 본 논문에서는 요청하고 있다. 아울러 법적인 지위를 보장하기 위한 현행 법령의 부재로 의무승선을 제도화 하였다 하더라도 결국 그 것을 집행하고 안전요원의 합법적 지위를 보장하기 위하여 법제도의 개선이 필요하나 입법의 부담과 이해관계인들 간의 합의가 쉽지 않을 것으로 판단되므로 현행 제도의 일부수정을 통해 안전요원의 법적지위 보장을 주장하는데 그 예로써 청원경찰법을 준용하는 방법을 제안해본다. 선박 내 안전요원을 청원경찰로서 이해한다면 승선한 안전요원의 의무와 교육과정, 고용 등에 대하여 보다 안정적으로 이행될 수 있을 것으로 판단된다. 이에 본 논문에서는 이와 같은 내용을 연안여객 이용률 등의 현황을 근거로 해당법률의 검토, 의무승선제도의 정의, 그리고 법적지위부여를 위한 청원경찰법의 준용 방법 등을 논하고 있다. On April 16th in 2014, Sewol Ferry carrying 476 passengers and crews including high school students for school excursion, capsized on the way to Jeju island from Incheon. By sinking off the coast suddenly, 295 people died and 9 people were missing. At that time, though all the nations waited for a safe return of people on board with best wishes, eventually it brought deep grief to all the families and other people by sinking into the cold sea. The large cargo ship accidents like this are usually not just caused by the problem itself but, rather, by lax management(omission) of managing authority such as shipping companies and government. We could not avoid the disaster due to the collective insolvency including the lacked expertise of captain and crews, careless cargo management, increase in authorized personnel on board by modifying vessel for maintaining benefit of shipping companies, and approval on an old ship in operation. In spite of the increasing number of passengers, the domestic coastal ferries can be limited from receiving the assistance of the public authorities unlike other means of transportation and therefore have a possibility of big accident than any other transportation. Thus, it is required to provide and prepare institutional system that made safety guides who completed professional training mandatorily ride the ferry together in order to immediately and actively cope with various accidents that may occur in service as well as a thorough pre-supervision of the competent authorities. Currently, for example, aircraft takes the professional security agents aboard and institutionalized armed security personnel on board so as to protect the personal safety of passengers and safe freight on an international fairway. Whereas, in the case of domestic ferries, while the shipping companies and government are aware of the necessity of duty aboard system of lifeguard, in terms of cost they do not continue to discuss due to the issue of equity on supporting tax revenues from the central government to the private sector, as small shipping companies cannot afford to pay more labor cost by employing more lifeguards. In this specification, this report examines the trend and transition of current coastal ferries and would like to emphasize the need for other duty aboard institutions of safety personnel. Also the legal system will be considered with legal status for the introduction of a compulsory system of security personnel on board. KCI Citation Count: 2